Summary - Nagy, Zoltán; Varga, Zoltán (Regulation of Public Finances in Light of Financial Constitutionality: Analysis on Certain Central and Eastern European Countries, 2022)
The chapter aims to summarise the main findings of the previous chapters from two viewpoints. First, it analyses the financial constitutionality in Central European countries, namely Hungary, Croatia, the Czech Republic and Slovakia, Poland, Romania, Serbia, and Slovenia. It can be concluded that in all countries legislation at the top of the hierarchy of legal sources regulates these issues. In Hungary we find the most important provisions on finance in the Fundamental Law; in the other countries in their constitutions. The Hungarian Fundamental Law regulates the issue in a separate section. The constitutions of the other countries include rules on the public finance system, however, in different depths. The second part of the chapter deals with budgetary rules in the examined countries. The act on the budget is one of the most important legal sources in each country, because financing is essential to the functioning of the state. The state’s revenues and expenditures are laid down by the budget in every country.KEYWORDS: Comparison, Constitution, Fundamental Law, budgetary rules, budget, national parliaments.